Effect of phototherapy on eosinophils count in neonatal hyperbilirubinemia (cross-sectional study) - Sara Tarek; Dalia S. Mosallam; Doaa Saber; Nehal Diaa; Omnia Y. Abd El Dayem; Samira Abdelmonem (SpringerOpen, 2023)
Abstract Background Neonatal jaundice is a common disorder in neonates. Phototherapy is associated with various side effects despite being safe. This research aimed to determine the impact of phototherapy (PT) on eosinophil levels in neonates treated for unconjugated hyperbilirubinemia. Methods In this cross-sectional prospective study, icteric neonates admitted to the Neonatal Intensive Care Unit (NICU) of Abo-Elreesh Child Hospital, Cairo University, from July 2020 to June 2021 were assessed. Laboratory data, including serum bilirubin and blood cell differentiation for eosinophils before and after phototherapy, were collected, and demographic data like age, gender, gestational age, and duration of phototherapy were taken. Results Two hundred neonates were included in this study. Hyperbilirubinemia was most frequently related to ABO group incompatibility (44.5%). After phototherapy, total serum bilirubin and neutrophil levels were significantly decreased, and platelet levels were significantly increased. Eosinophil count and percent were significantly increased (p < 0.001) following phototherapy. A statistically significant positive correlation was found between eosinophil count before and after PT (r = 0.583, p < 0.001) and between eosinophil percent before and after PT (r = 0.617, p < 0.001). Conclusion Serum eosinophils were increased after phototherapy in icteric neonates with hyperbilirubinemia.